الإصلاحات السياسية و آفاق الانتقال الديمقراطي في الجزائر (El-Wahat Journal for Research and Studies, 2025)
The Subject Of The Study Is Of Great Importance Because It Analyzes The Various Political Reforms That Algeria Has Witnessed, And Searches For Their Adequacy To Achieve A Real Democratic Transition. Political Reforms, And The Historical Method Was Relied Upon To Collect Information, Facts And Events Necessary To Reveal The Conditions And Reasons That Led To Political Reforms, And The Study Concluded That Despite The Importance Of Political Reforms That Algeria Knew After The Popular Movement, It Remains Insufficient To Achieve A Democratic Transition, Key Words: democratic transition, political reform, constitutional amendment, political transformation.